Parkinson's disease-related DJ-1 functions in thiol quality control against aldehyde attack in vitro. Issue 1 (December 2017) - Matsuda, Noriyuki; Kimura, Mayumi; Queliconi, Bruno Barros; Kojima, Waka; Mishima, Masaki; Takagi, Kenji; Koyano, Fumika; Yamano, Koji; Mizushima, Tsunehiro; Ito, Yutaka; Tanaka, Keiji
Abstract DJ-1 (also known asPARK7 ) has been identified as a causal gene for hereditary recessive Parkinson's disease (PD). Consequently, the full elucidation of DJ-1 function will help decipher the molecular mechanisms underlying PD pathogenesis. However, because various, and sometimes inconsistent, roles for DJ-1 have been reported, the molecular function of DJ-1 remains controversial. Recently, a number of papers have suggested that DJ-1 family proteins are involved in aldehyde detoxification. We found that DJ-1 indeed converts methylglyoxal (pyruvaldehyde)-adducted glutathione (GSH) to intact GSH and lactate. Based on evidence that DJ-1 functions in mitochondrial homeostasis, we focused on the possibility that DJ-1 protects co-enzyme A (CoA) and its precursor in the CoA synthetic pathway from aldehyde attack. Here, we show that intact CoA and β-alanine, an intermediate in CoA synthesis, are recovered from methylglyoxal-adducts by recombinant DJ-1 purified fromE. coli . In this process, methylglyoxal is converted to L-lactate rather than the D-lactate produced by a conventional glyoxalase. PD-related pathogenic mutations of DJ-1 (L10P, M26I, A104T, D149A, and L166P) impair or abolish detoxification activity, suggesting a pathological significance. We infer that a key to understanding the biological function of DJ-1 resides in its methylglyoxal-adduct hydrolase activity, which protects low-molecular thiols, including CoA, from aldehydes.